Advances in experimental phasing. Issue 3 (1st March 2016) - McCoy, Airlie J.; Schneider, Thomas
Abstract : An introduction to the 2015 CCP4 Study Weekend on Advances in Experimental Phasing. Abstract : An introduction to the 2015 CCP4 Study Weekend on Advances in Experimental Phasing.